Facial fractures by bicycle accidents in pediatric and adolescent patients - Muñante-Cárdenas, José (2011)
The aim of this study was a retrospective analysis of the incidence, characteristics, use of safety devices, treatment and complications of maxillofacial trauma caused by bicycle accidents in a pediatric and adolescent population of São Paulo. The sample was selected from analysis of 2986 medical records of victims of facial trauma patients treated entre1999 and 2008 by the Department of Oral and Maxillofacial Surgery, Piracicaba Dental School, State University of Campinas, São Paulo, Brazil. During this period, 757 patients under 18 years were treated, of which 220 were victims of bicycle accidents. The bicycle accidents constituted the main etiology (29 %) of facial trauma. Only 1.8% of patients made use of safety devices. The adolescents group and male gender were the most prevalent in all age groups evaluated. Were identified 69 facial fractures, being jaw the most affected (55.1 %). Conservative treatment was used in the most of cases (50 patients 72.4 %), while only one case of postoperative complication was reported.